Interactive Digital Module for Elementary School Science and Social Studies Learning Using the Multimedia Development Life Cycle Method - Putra, Kurnia Ramadhan; Angelica, Evlyn; Adinda, Najwa; Rahmainingtias, Berka Ridha; Putri, Azzahra Candra; Utami, Azzila Deswita; Purwanti, Tri Rahayu; Putri, Windi Laudi; Wahidyah, Nazillah; Abigael, Hugo; Risyanti, Rifa Aulia (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2025)
This Community Service Program (PKM) addresses challenges in implementing interactive learning technology at SDN 150 Gatot Subroto, focusing on grades 4 and 5. It develops multimedia-based modules and provides teacher training using the Multimedia Development Life Cycle (MDLC) method, comprising five stages: initialization, blueprint design, asset preparation, product development, and testing. The modules include animations, navigation buttons, background music, and interactive quizzes to enhance student motivation and understanding. A SWOT analysis highlights strengths such as PowerPoint’s accessibility and the growing awareness of technology-based learning. However, infrastructure limitations and teacher resistance to technology pose challenges.Testing with 54 students showed over 50% could correctly answer quizzes, indicating the media effectively improves comprehension. The program concludes that interactive multimedia-based learning enhances student motivation and engagement. Recommendations include providing guide modules, regular teacher training, and teacher learning groups to support sustainable implementation. This program offers a lasting solution to improving elementary education through interactive multimedia.